Pitcher-plants of Borneo - Phillips, A.; Lamb, A. (Malaysian Journal of Science, 1996)
Although there are a number of books on the general subject of Carnivorous Plants, within which there would be a section on Nepenthes (commonly referred to as tropical pitcher plants), there are very few solely devoted to the topic of Nepenthes plants. This new book "Pitcher-plants of Borneo" makes a much-needed contribution to the general knowledge of, and interest in, these plants.